On fundamental sets over a finite field - Yousef Abbas; Joseph J. Liang (International Journal of Mathematics and Mathematical Sciences)
A partition over finite field is defined and each equivalence class is constructed and represented by a set called the fundamental set. If a primitive element is used to construct the addition table over these fundamental sets then all additions over the field can be computed. The number of partitions is given for some finite fields.